PEMBERDAYAAN UMKM INDUSTRI RUMAHAN OLAHAN DAUN KELOR “KELORASA” DI DESA PURWOASRI KECAMATAN GUMUKMAS KABUPATEN JEMBER - Durrotun Nasihin; Kartika Rahayu Ningdiah; Tita Saskia Asmoro; Husnul Khotimah; M Afriyanto; Pandu Satriya Hutama (LPPM Universitas Bina Bangsa, 2022)
Purwoasri Village, Gumukmas District, Jember Regency has a fairly large area of plantations and rice fields. This makes the produce produced abundantly so that it becomes a diverse commodity and has promising economic potential if processed creatively and innovatively. One of the residents of Purwoasri village succeeded in processing the abundant Moringa plant into various unique and good processed products for health such as the moringa tubruk, the Moringa dip, and Moringa flour. The processing of Moringa plants into various unique products goes through several systematic and sterile processes such as picking, separation of leaves and stems, washing, spinning process or reduction of moisture content, drying, the process of smoothing Moringa leaves into powder and flour, and packaging. Nevertheless, the success of processing Moringa plants into innovative products is also accompanied by marketing limitations which are obstacles for business owners. The purpose of this service is to empower the home industry of moringa plant processing located in Purwoasri Village, Gumukmas District, Jember Regency in the field of promotion and marketing. The method used is the real method by surveying directly to industrial places and applying solutions that have been researched and discussed